Sap flow of pecan trees in a US Southeastern orchard - Zhang, Gengsheng; Leclerc, Monique Y.; Wells, Lenny (Frontiers in Agronomy, 2025)
Sap flow methods are widely used to estimate water use through transpiration in orchards. This study reports for the first time on pecan tree sap flow properties observed in a micro-irrigated orchard in the southeastern US in 2022 and 2023. This new information regarding sap flow properties of Southeastern pecan trees sheds some insight on how pecan water use responds to environmental conditions. The daily peak in the sap flow density occurs either before or after the peak in diurnal solar radiation. The latter peaks before that of air temperature and vapor pressure deficit while the peaks of air temperature and vapor pressure deficit occur later than that of solar radiation. Seasonally, the largest sap flow density occurred during both the growth stage of early nut sizing in May-July and the growth stage of nut sizing and early kernel filling in July-August. The sap flow density in 2022 was higher than that in 2023 mainly due to higher vapor pressure deficit that year. While a single anticlockwise loop of hysteresis occurred in the sap flow diurnally varying with solar radiation in 2023, a twin loop of hysteresis of sap flow to solar radiation was observed in 2022. The twin loop happened since the sap flow peak occurred earlier than that of solar radiation, possibly attributed to high morning vapor pressure deficit that year. A single clockwise loop hysteresis was present in both years in the response of sap flow to air temperature and vapor pressure deficit. The hysteretic strength of the sub-diurnal sap flow density against the vapor pressure deficit for the Southeastern pecan is quantified using a hysteresis index. The index is correlated positively with vapor pressure deficit. This suggests that the drier the air, the greater difference for pecan tree sap flow (or transpiration) in the afternoon to be smaller than that in the morning at the same vapor pressure deficit.